Potential of avocado oil (Persea americana) in improving triglyceride and High Density Lipoprotein (HDL) levels in rats (Rattus novergicus) model of dyslipidaemia due to high fat diet - Sari, Eka Puspita; Wasita, Brian; Muthmainah, Muthmainah (Alma Ata University Press, 2024)
Background: Elevated levels of Dyslipidaemia pose a significant threat to cardiovascular health. Fortunately, the abundance of polyunsaturated and monounsaturated fatty acids (PUFA and MUFA) present in avocado oil offers a promising avenue for individuals with Dyslipidaemia to improve their lipid profile levels.Objectives: The objective of this research is to ascertain the potential of avocado oil in improving triglyceride and HDL levels.Methods: A pre-post test control group design was employed, utilizing male Wistar rats aged 8 weeks with a body weight ranging from 150-200 g. The mice were segregated into six groups: N, K-, K+, P1, P2, and P3. Throughout the trial, solely group N abstained from ingesting avocado oil or HC. Conversely, all other groups were administered HC and subsequently, K+ was prescribed simvastatin while P1, P2 and P3 received avocado oil for a duration of 28 days. The data was subjected to statistical analysis using SPSS vr.25. The statistical significance threshold was set at p<0.05.Results: Mean changes in levels (mg/dL) for TG -29.67 (P1), -48.99 (P2), -56.78 (P3) and for HDL 41.75 (P1), 46.35 (P2). There was a significant difference in TG and HDL levels between P1, P2, P3 when compared with K- (p<0.05).Conclusion: Avocado oil exhibits efficacy in lowering TG levels and elevating HDL levels, rendering it a viable option for daily consumption.